Development of Learning for Memorizing Surah Al-Ma'un Based on Puzzle Game for Seven-Year-Old Children - Nurchari, Muadz Rasyid; Faradiella, Elvynanda; Fiddarain, Zaduna; Nabila, Laili; Fitria, Laila Annis; Asmoro, Secoundio Rabbanissa (Universitas Muhammadiyah Surakarta, 2023)
The Quran education in early childhood is an integral part of an achievement aiming to develop potential in children. Innovative game-based approaches have been introduced to improve the effectiveness of Quran learning, one of which is through puzzle-based games. The author tries to analyze the strategies applied in integrating gaming technology into the context of learning the Koran. A qualitative study is likely sufficient to identify improvements in children's participation and learning results in memorizing the Quran. Hopefully, puzzle-based game learning technology can develop and improve children's enthusiasm and focus while memorizing the Quran.